PERILAKU IBU DALAM KEGIATAN PENIMBANGAN BALITA DI KABUPATEN SIGI PROPINSI SULAWESI TENGAH TAHUN 2012 - Esron Sirait; I Kadek Wartana (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2012)
The aim of This study was to identify factors suspected have the relation on mother behavior to weigh her under years five children in Sigi District of Centra Sulawesi. Sigi District was selected as the study are based on the coverage of the five years children weighing relatively lower than other District in Central Sulawesi. The type of this study was an analytic research with cross sectional approach November 23rd December 2010-February 21st 2012. The subject were 2086 mother chocen by cluster random sampling. Data was obtained by questionaries that contructed based on the weigh her under five years children. Data were analized by sperman rank correlation coeficient test. The result showed that mather’s perception on the seriousness of diseases, benefit of weighing under five years children, and the frequencies to obtained information about nutrition had the relation with mother’s behavior to weigh her under five children. The role of cadres provingding encouragement to motivate mother in order to weigh her under five years children was the first rank, followed by health officials in the second one.